The anatomy of competitiveness - Thomas Buser; Hessel Oosterbeek (Tinbergen Institute, 2023)
A large empirical literature in behavioral economics investigates heterogeneity across individuals and groups in preferences for competition. In this study, we provide a more detailed view on competitiveness by differentiating between four different motivations for entering competitions – enjoyment of competition, desire to win, competition for personal development, and general challenge seeking. We investigate which of these dimensions are picked up by traditional measures of competitiveness; how they predict individual and gender differences in career outcomes including income, holding a leadership position, and entrepreneurship; how they predict wellbeing; and how they relate to other personality traits, skills, and preferences.
Keywords: C92; D91; J24; 330; competitiveness; personality traits; labor market outcomes; leadership; gender